Masculinities in Old Norse Literature. Eds. Gareth Lloyd Evans, Jessica Clare Hancock. Cambridge, D.S. Brewer, 2020, ss. 285 - Jakubczyk, Radosław (Średniowiecze Polskie i Powszechne, 2021)
Masculinities in Old Norse Literature. Eds. Gareth Lloyd Evans, Jessica Clare Hancock. Cambridge, D.S. Brewer, 2020, ss. 285